Structural Synthesis in the Frequency Domain: A General Formulation - Joshua H. Gordis (Shock and Vibration)
A general formulation for frequency domain structural synthesis is presented. The formulation is based on a physical coordinate transformation of the presynthesis frequency response system model and addresses modification, general coupling, and constraint imposition. Notable features of the formulation includes the ability to directly synthesize response quantities such as displacements, stresses, and strains, and the accommodation of Boolean matrices that organize the connectivity in the synthesis of complex systems. The theory is shown to be a highly efficient and exact means of doing static and complex dynamic reanalysis.